2002
DOI: 10.1084/jem.20011825
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the In Vivo Role of a Viral bcl-2

Abstract: Many γ-herpesviruses encode candidate oncogenes including homologues of host bcl-2 and cyclin proteins (v-bcl-2, v-cyclin), but the physiologic roles of these genes during infection are not known. We show for the first time in any virus system the physiologic role of v-bcl-2. A γ-herpesvirus v-bcl-2 was essential for efficient ex vivo reactivation from latent infection, and for both persistent replication and virulence during chronic infection of immunocompromised (interferon [IFN]-γ−/−) mice. The v-cyclin was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
159
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(170 citation statements)
references
References 56 publications
(115 reference statements)
10
159
1
Order By: Relevance
“…42 Yet other work suggests that BCL-2 homologs are more important for reactivation or persistent infection. 43 Their role in cancer is equally undecided, and understanding has been limited by the poor availability of good antibodies recognizing the proteins. However, transcripts of KSHV BCL-2 have been detected in cell lines and clinical samples from primary effusion lymphoma and KS.…”
Section: Discussionmentioning
confidence: 99%
“…42 Yet other work suggests that BCL-2 homologs are more important for reactivation or persistent infection. 43 Their role in cancer is equally undecided, and understanding has been limited by the poor availability of good antibodies recognizing the proteins. However, transcripts of KSHV BCL-2 have been detected in cell lines and clinical samples from primary effusion lymphoma and KS.…”
Section: Discussionmentioning
confidence: 99%
“…Viruses also target the Bcl-2 family (56), and roles for apoptosis in both the propagation and suppression of virus replication have been described (1). With few exceptions (40), however, the in vivo functions of these proteins are largely unknown. Lytic viruses may utilize host apoptotic cascades to aid in cell destruction and virus dissemination, and cells counter with sensitive detection systems to attempt to short circuit replication by undergoing an "altruistic" apoptosis before the virus has completed the entire replication process (53).…”
Section: Fig 6 Effect Of Noxa On Ifn Sensitization Of Cells To Apopmentioning
confidence: 99%
“…Dysregulation of these processes helps the virus to survive and successfully replicate. Recent in vivo work has shown that the gammaherpesvirus expresses several cellular protein mimics including a viral-cyclin and a viral-bcl-2 that are critical for viral reactivation from latency and replication in immunocompromised hosts (5). Furthermore, these viral genes likely increase the propensity for oncogenic transformation of virus-infected cells based on their ability to interfere with established tumorsuppressor pathways (2).…”
mentioning
confidence: 99%